2017
DOI: 10.1371/journal.pone.0178775
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo comparison study in goats for a novel motion-preserving cervical joint system

Abstract: Cervical degenerative disease is one of the most common spinal disorders worldwide, especially in older people. Anterior cervical corpectomy and fusion (ACCF) is a useful method for the surgical treatment of multi-level cervical degenerative disease. Anterior cervical disc replacement (ACDR) is considered as an alternative surgical method. However, both methods have drawbacks, particularly the neck motion decrease observed after arthrodesis, and arthroplasty should only be performed on patients presenting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous studies compared the clinical outcome of ACDF and ACCF in 2-level cervical spondylosis myelopathy and found no difference in adjacent-level ossification and complications [24], suggesting that neither ACDF nor ACCF perform better in the degenerative changes in the adjacent levels, and other techniques, such as use of an anterior non-fusion fixation device, should be considered to address this problem [25].…”
Section: Adjacent-level Complicationsmentioning
confidence: 99%
“…Previous studies compared the clinical outcome of ACDF and ACCF in 2-level cervical spondylosis myelopathy and found no difference in adjacent-level ossification and complications [24], suggesting that neither ACDF nor ACCF perform better in the degenerative changes in the adjacent levels, and other techniques, such as use of an anterior non-fusion fixation device, should be considered to address this problem [25].…”
Section: Adjacent-level Complicationsmentioning
confidence: 99%
“…Micro-CT and bone tissue analysis revealed that osteogenesis in the uncovertebral joint was greater than that in the end-plate space 21 . The goat cervical spine resembles the human cervical spine anatomically, making it suitable for spine-related research [29][30][31] . A large-sample, longterm follow-up study of cervical disc replacement found that high-grade paravertebral ossification mainly occurred in the bilateral uncovertebral joint regions 32 .…”
Section: Discussionmentioning
confidence: 99%